Company Structure and Level of Service of Syarikat Air Darul Aman (SADA) To Consumers in Kedah - Othman, Muhammad Fuad; Zulkifli Zainuddin, Abd. Ghani@; Shukri, Shazwanis; Islam, Rabiul (International Journal of Membrane Science and Technology, 2023)
The purpose of the study was to assess the function of the water supply treatment and distribution company in the state of Kedah, Syarikat Air Darul Aman (SADA) in fulfilling its function of supplying clean and treated water to 2.2 million people in Kedah. Despite the company structure, the impact of legislative regulation under the act of parliament and state enactment resulted in SADA being subject to full political control even though it is a business entity in accordance with the Companies Act 1965. For this purpose, 200 respondents were taken at random and distributed questionnaires in three SADA operating centres covering three regions, namely Eastern, Southern and Northern Kedah Regions 1. Four themes were observed using descriptive statistical analysis which is about the user's understanding of SADA functions. It also involves consumer expectations on SADA, the level of satisfaction with over-the-counter services and operations. The findings found that on average the percentage of user satisfaction in relation to the service and orientation provided by SADA was still poor. The level of professionalism, effective service and corporate governance is still underappreciated as the dominant culture in SADA due to the overshadowed company structure of a government agency.